Implications of in-band crosstalk on DQPSK Signals in ROADM-based metropolitan optical networks - Cancela, L. G. C. (2016)
Metropolitan optical networks can be designed to transport a multitude of signals with different bit rates and modulations formats. In this way, in-band crosstalk signals, originated from imperfect isolation inside ROADM (Reconfigurable Optical Add and Drop Multiplexer)-based optical nodes, will potentially have a different modulation format than the primary signal. In this paper, the origin of in-band crosstalk in a typical ROADM is analysed and its impact on differential quadrature phase-shift keying (DQPSK) signals is assessed through an analytical formalism based on the moment generating function (MGF) of the receiver decision variable. Various scenarios are analysed including the case of multiple interfering terms with different modulation formats, namely the on-off keying (OOK). It is concluded that the OOK interferer is more detrimental than the DQPSK interferer for DQPSK systems, or than the differential phase-shift keying (DPSK) interferer for DPSK systems.